Whose community? which interpretation?: philosophical hermeneutics for the church - Westphal, Merold (The church and postmodern culture, 2009)
Hermeneutics 101: no interpretation needed? -- Hermeneutics 102 : a little historical background -- Against romantic hermeneutics : away from psychologism -- Objectivism and authorial privilege -- Revoking authorial privilege -- Rehabilitating tradition -- On not clinging to the prejudice against prejudice -- Art as the site of truth beyond method -- Performance, application, conversation -- Conversation and the liberal-communitarian debate -- The church as conversation -- Transcendence, revelation, and community